(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is devoted to the expression of subject indefiniteness with lexico-grammatical parts of words in English and Uzbek languages. The expression of indefiniteness of the subject in the system of different languages with lexico-grammatical parts of words have been analyzed and its similarities and differences are identified.